1991
DOI: 10.1002/mpo.2950190411
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of meningeal leukemia when prednisone is replaced by dexamethasone in the treatment of acute lymphocytic leukemia

Abstract: In 1971, Cancer and Leukemia Group B (CALGB) mounted a study of acute lymphocytic leukemia (ALL) that compared the effects of the two steroid hormones dexamethasone and prednisone. Six-hundred-forty-six children and adolescents with ALL were randomized to receive either prednisone or dexamethasone as part of their remission induction therapy. The 493 evaluable patients who achieved complete remission received the same steroid as pulses throughout remission. Specific central nervous system (CNS) therapy was ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 27 publications
2
74
0
2
Order By: Relevance
“…Of these, eight studies satisfied eligibility criteria and were included in the metaanalysis. [6][7][8][9][14][15][16]22 The reviewers had perfect agreement on articles for inclusion, with a k statistic of 1.0. The reasons for excluding 15 articles are shown in Figure 1.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, eight studies satisfied eligibility criteria and were included in the metaanalysis. [6][7][8][9][14][15][16]22 The reviewers had perfect agreement on articles for inclusion, with a k statistic of 1.0. The reasons for excluding 15 articles are shown in Figure 1.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…7,9 Blinding status was not reported by any study. Withdrawal information could be retrieved from four of the eight, [6][7][8]22 and intention-to-treat analysis was reported for three trials 6,8,14,16 (Supplementary Data B).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Branimir Jaksic, 8 Walter Feremans, 9 Dominique Bron, 10 Harm Sinnige, 11 Martin Mistrik, 12 Gerard Vreugdenhil, 13 Robrecht De Bock, 14 Damir Nemet, 1 Caroline Gilotay, 2 Sergio Amadori, 15 …”
mentioning
confidence: 99%
“…Recently, plasma and CSF concentration-time profiles after an intravenous bolus dose of prednisolone phosphate were measured in three rhesus monkeys by Balis et al (1987). The CSF concentrations of prednisolone were very low and it was suggested that this might be one reason for the poor efficacy of prednisolone in the treatment of central nervous system leukemia in man (Jones et al, 1975(Jones et al, , 1984. The purpose of the present study was to investigate the relationship between prednisolone concentrations in plasma and CSF in humans after intravenous administration of equimolar doses of two prednisolone prodrugs, prednisolone phosphate and prednisolone phthalate.…”
Section: Introduction Methodsmentioning
confidence: 99%